Échecs et réussites discursives du mouvement #MeToo - Noémie Trovato (Glad!)
This article, set in the field of digital discourse analysis and Gender & Language Studies, proposes to think about #MeToo discursive successes and failures through the examination of various tweets (testimonies, criticisms by feminist activists and news from the press). Since 2017, the #MeToo movement has been depicted as effective, it allegedly liberated women’s speech about the sexual violence they experience throughout their lives. I aim to relativize this claim by interrogating the performative dimension of #MeToo as intended and perceived by victims and feminist activists. To do so, I analyze the hashtag’s polyvalence, used as a praxonym and as a brand, as well as the conditions of emergence of the movement, which has been sedimented and fragmented by the launch of around twenty different hashtags.